Being Human During COVID-19 - Martin, Paul; de Saille, Stevienna; Liddiard, Kirsty; Pearce, Warren (Bristol University Press, 2022)
The digital pdf version of Chapter 12 is available Open Access under CC-BY licence. This transdisciplinary collection engages with key issues of social exclusion, inequality, power and knowledge in the context of COVID-19. Putting the spotlight on the lived experiences of marginalised groups from around the world, the authors reframe ongoing debates around the pandemic and highlight how they might lead to new ways of thinking and acting in relation to public policy, culture and the economy.